Penataan Ulang Ruang Parkir Lapangan Terbuka “Mail Giant”, Cimanggis Bogor - Utama, Dwinanta (Warta Penelitian Perhubungan, 2010)
Drivers moving from an origin to destination at one time and at certain place will need to stop theirvehicles Vehicle that stop for parking will need a safe and comfortable place to assure that it will notobstnt.ct the other traffic movement.Giant Mall as a shopping center at Cinuznggis Bogar 1iritlz existing parking capacihj of 250 cars and273 motora1cles is facing parking problem, so it needs some reuiew design. During the peak hour inweekend time, it shows that more vehicles come in to be parked th.en the maximum capacity parkinglot prcmi.ded. Hopefully bt; having a redesign parking improvement this problem can be solved toobtain better condition.